2016
DOI: 10.1002/em.22021
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral radiation mitigation to standard brain cancer therapy regimens by Mn(III) n‐butoxyethylpyridylporphyrin‐based redox modifier

Abstract: Combinations of radiotherapy (RT) and chemotherapy have shown efficacy toward brain tumors. However, therapy-induced oxidative stress can damage normal brain tissue, resulting in both progressive neurocognitive loss and diminished quality of life. We have recently shown that MnTnBuOE-2-PyP(5+) (Mn(III)meso-tetrakis(N-n-butoxyethylpyridinium -2-yl)porphyrin) rescued RT-induced white matter damage in cranially-irradiated mice. Radiotherapy is not used in isolation for treatment of brain tumors; temozolomide is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 41 publications
(74 reference statements)
1
32
0
Order By: Relevance
“…Our previous studies showed MnBuOE to be efficacious in reducing normal tissue injuries and enhancing sensitivity of cancers to radiation and chemotherapies [13], [20], [21], [23], [47], [48]. This study expands the normal tissue benefits of MnBuOE to post-irradiation hippocampal neurogenesis, and provides a strong translational support for the current clinical trial of using MnBuOE as a radioprotector.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Our previous studies showed MnBuOE to be efficacious in reducing normal tissue injuries and enhancing sensitivity of cancers to radiation and chemotherapies [13], [20], [21], [23], [47], [48]. This study expands the normal tissue benefits of MnBuOE to post-irradiation hippocampal neurogenesis, and provides a strong translational support for the current clinical trial of using MnBuOE as a radioprotector.…”
Section: Resultssupporting
confidence: 57%
“…Based on previous pharmacokinetics, toxicology, and efficacy studies [11], [13], [20], [21], [24], [25], a daily dose of 3 mg/kg of each MnP was used. Mice received either two daily subcutaneous (sc) injections (2×1.5 mg/kg) for 7–14 days, or continuous infusion for 2–6 weeks using a model 1004 Alzet® osmotic pump loaded with 28.4 mg/ml MnP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of the relationship among oxidative stress, disruptions in CNS function and exposure to radiation or specific classes of chemical carcinogens is emphasized in three articles in this special issue [Chmielewski et al, ; Lemon et al, ; Weitzel et al, ]. These articles highlight interventions that can ameliorate the functional decrements caused by radiation and chemotherapy by reducing oxidative stress.…”
mentioning
confidence: 99%